Comparing the richness in the beauty articles of ELLE and seventeen magazines - Deny A. Kwary, Rani Y. Astiti (Opción, 2019)
This study presents the result of lexical richness analysis which is aimed to see the difference of language variation and use across age groups via lexical density analysis, lexical sophistication analysis and lexical variation/ diversity analysis as methods. The result of the analysis shows that there is no significant difference in the lexical density of ELLE and Seventeen magazines. From TTR analysis, we conclude that the register or the genre of the text does not affect TTR.